Is Arthrodesis a Reliable Salvage Option following Two-Stage Revision for Suspected Infection in Proximal Tibial Replacements? A Multi-Institutional Study - Sambri, Andrea; Bianchi, Giuseppe; Parry, Michael; Frenos, Filippo; Campanacci, Domenico; Donati, Davide; Jeys, Lee (The Journal of Knee Surgery, 2019)
The aim of this multicentric retrospective study was to verify whether knee arthrodesis (KA) is a viable reconstructive option after two-stage revision for infection of proximal tibia (PT) endoprosthetic reconstruction (EPR). Sixty patients who underwent a two-stage revision were included. Definitive EPR or a KA with a modular system was performed following consideration of soft tissue and extensor mechanism conditions. Patients were evaluated with Musculoskeletal Tumor Society Score and Oxford Knee Score. Implant survival was assessed on the basis of recurrence of infection. Five patients did not receive any reconstruction after the first stage. In 14 cases, a KA was performed, and in 41, an EPR was implanted. At 5 years follow-up, reinfection rate in the KA group was lower (10 vs. 17.5% in KA and EPR groups, respectively). In reinfected patients, the KA group had a reduced rate of amputation when compared with those with EPR (50 vs. 88%). Functional evaluation did not show any significant differences between the two groups. A successful KA using a modular implant can eradicate infection and allow preservation of the limb with good function and good pain relief in after two-stage revision for an infected PT EPR.
Keywords: infection; proximal tibia; endoprosthetic replacement; knee arthrodesis; bone; sarcoma